Soy-based adhesives for wood-bonding – a review. Issue 8 (18th April 2017) - Vnučec, Doroteja; Kutnar, Andreja; Goršek, Andreja
Abstract: Over recent years, the interest in bio-adhesives, including soy-based adhesives, has increased rapidly. Among natural renewable resources suitable for industrial use, soy is a reasonable choice due to its high production volume and the small use of soy meal-based products for human food consumption. Soy flour can be an ideal raw material for the manufacturing of wood adhesives due to its low cost, high protein content and easy processing. There are also more concentrated forms of soy proteins, i.e. concentrates and isolates, which are also suitable raw materials for adhesive production except that their prices are higher. Extensive research has been carried out on improving the cohesive properties, especially water resistance, of soy-based adhesives. However, there is insufficient experimental data available for understanding the influences of modification methods on the structure of soy proteins and therefore for understanding the influences of structural changes on the adhesion. In this paper, some experimental techniques are proposed to be used for analysing soy-based adhesives to enable better understanding of those factors and improve future development. This review of soy-based adhesives is made with the focus on soy proteins' chemical composition, soy protein product types (raw materials for adhesive production), modification methods for improving the adhesive properties of soy-based adhesives, and commercial soy-based adhesives.